THE TRADITION OF BEHAUH NGANTOK FROM BETINO CHILDREN TO TENGGANAI AHEAD OF THE MONTH OF RAMADAN IN THE RAWANG HAMPARAN COMMUNITY - Ramadani, Yolla; _, Hafizah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
The tradition of Ngantok Behauh from Anak Betino to Tengganai ahead of the month of Ramadan in the Hamparan Rawang community is a tradition of delivering rice or other basic necessities from sisters to Tengganai or brothers. The Ngantok Behauh tradition is still carried out by the people of Hamparan Rawang to this day. This research aims to describe the implementation process, find out the meaning and understand the values ​​contained in Ngantok Behauh in the Hamparan Rawang community. The data analysis used in this research is ethnographic analysis from Clifford Geertz, data hermeneutics, interpreting data, and interpretive representation. This research shows that the Ngantok Behauh tradition is a tradition passed down from generation to generation which is still carried out by the Hamparan Rawang community to this day. This tradition is still maintained by the community because it contains values ​​and meanings that are shared by the entire community. The values ​​contained in the Ngantok Behauh tradition include: brotherhood values, social values ​​and local wisdom values. Apart from this, the tradition of ngantok behauh also has the meaning of strengthening friendly relations between families as well as respecting male children who will always be ready to help female children solve any problems they encounter later.